Preliminary results on the somatic and body compositional changes in juvenile common carp during long-term starvation - Varga, Dániel; Hancz, Csaba; Molnár, Tamás; Romvári, Róbert; Szabó, András (Acta Agraria Kaposváriensis, 2014)
The aim of our study was to analyse the body compositional changes in common carp juveniles during 12-week-long starvation. Food restriction had a significant impact on every parameter. Hepatosomatic index, viscerosomatix index and condition factor decreased linearly, while in case of body composition parameters a slight fluctuation can be observed. Body fat and dry matter content decreased, protein and ash increased due to 12-week-long starvation. It can be concluded that body lipids constituted the major energy source for starved carp juveniles and 12-week-long starvation did not induce proteolysis in tissues.
Keywords: common carp; juveniles; body composition; starvation